Pengaruh Inflasi dan Pengeluaran Pemerintah terhadap Pertumbuhan Ekonomi - Harahap, Rifqah; Syahidin; Jalil, Abd; Ramadhan, Masri; Kartika, Erawati (Jurnal EMT KITA, 2025)
Research to analyze the effect of inflation and government spending on economic growth. Data analysis with Eviews 12. The data used is secondary data in the form of annual data sourced from the official website of the Central Statistics Agency for 2016-2023. The results of the data analysis show that the variables of inflation, government spending simultaneously have a positive and significant effect on economic growth. Partially, the government spending variable has a significant effect on economic growth, while inflation does not have a significant effect on economic growth in Indonesia. The R-squared value of 0.8977 means that the magnitude of the influence of the independent variable on economic growth is 89.77%.
Keywords: Economic Growth; Inflation; Government Spending; Indonesia